Analisis Pengembangan Sumber Daya Amil Pada Rumah Zakat Surabaya: Pendekatan Balanced Scoredcard - basar dikuraisyin (STES Islamic Village, 2021)
The effort of this study to analyzed the competence of amil zakat institutions based on performance and accountability. This analysis was important because amil as determinant of productivity and the success of zakat management. Meanwhile, the reality of amil's performance in Indonesia, still showed an alarming performance. The principles of accountability and competence as regulated where still not detailed. Impacted on the irregularity of the institutional concept of zakat management so far. Therefore, this study answered how the analysis of the Balanced Scorecard approach toward the competence and accountability of amil in zakat institutions. This research was approached in a qualitative analytical regulations, the primary source was obtained from the amil work system with the Balanced Scorecard analysis as the embodiment of the evaluation approach. Data were obtained through documentation, interviews with systematic standard guidelines. After conducting the research, important inventions were found, namely: the first, the performance of amil at LAZ Rumah Zakat adheres to the principle of proportional balance and autonomy based both on the work aspects of amil as well as mustahik and muzakki. The second, the results of the balance scores card analysis on the competence of amil zakat in LAZ Rumah Zakat produced findings: 1) financial perspective, LAZ Rumah Zakat was said effective because there where indications of an increasing every year both in the aspects of raising funds, the number of muzakki and the reduction of mustahik. 2) customer perspective (mustahik-muzakki), mustahik was pleased with the protection and assistance of LAZ Rumah Zakat. 3) internal business perspective, namely the planning that made by LAZ Rumah Zakat suitable for the reality in the field. 4) needs and learning perspective, amil's performance in each division worked optimally and helped each other